2006
DOI: 10.1080/03079450600597865
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bronchitis virus S1 gene sequence comparison is a better predictor of challenge of immunity in chickens than serotyping by virus neutralization

Abstract: Five strains of infectious bronchitis virus isolated from commercial chickens from the state of Pennsylvania, USA during the years 1998 and 1999 were studied. The strains were selected for cross-challenge in specific pathogen free chickens and virus neutralization in chick embryos on the basis of partial S1 sequence amino acid identity values. The partial sequences analysed spanned the hypervariable amino terminus region of S1 from amino acid residues 48 to 219, based on the Beaudette strain. Using their S1 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 36 publications
(44 reference statements)
2
50
0
2
Order By: Relevance
“…All of these isolates came from flocks vaccinated with Massachusetts-type vaccines, which produced insufficient protection against these field strains. As noted by Ladman et al (2006), there is a strongly correlation between the sequence including HVR1/2 of S1 with protective relatedness values, more than antigenic relatedness values based on virus neutralization and haemagglutination inhibition. These observations and the poor relationship between the Argentinean field isolates (from clusters A, B and C) and Massachusetts vaccine strains (average amino acidic identity of 73.6% between clusters A, B and C when compared with the Massachusetts group) could explain the failure of the Massachusetts serotype vaccination programmes to control IBV in these flocks (Gelb et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…All of these isolates came from flocks vaccinated with Massachusetts-type vaccines, which produced insufficient protection against these field strains. As noted by Ladman et al (2006), there is a strongly correlation between the sequence including HVR1/2 of S1 with protective relatedness values, more than antigenic relatedness values based on virus neutralization and haemagglutination inhibition. These observations and the poor relationship between the Argentinean field isolates (from clusters A, B and C) and Massachusetts vaccine strains (average amino acidic identity of 73.6% between clusters A, B and C when compared with the Massachusetts group) could explain the failure of the Massachusetts serotype vaccination programmes to control IBV in these flocks (Gelb et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, less than 79.4 and 81.1% of nucleotide and amino acid similarities in S1 part of spike protein were shared, respectively, by the vaccine strains and isolate tl/CH/LDT3/03, which represents the major type of nephropathogenic IBV isolate present in the field in China, and was of a different serotype from the vaccine strains used here, indicating the various antigenic differences and larger evolutionary distances between vaccine strains and IBV strains present in the field. Although it has been reported that IBV S1 gene sequence comparison is a better predictor of challenge of immunity in chickens than serotyping by virus neutralization (Ladman et al, 2006), it is probably of more practical relevance in terms of control strategies to perform protection studies (protectotype) with the field isolates (Lohr, 1988;Cook et al, 1999). Of the eight vaccine strains sequenced in this study, four were selected for vaccination-challenge trials.…”
Section: Discussionmentioning
confidence: 99%
“…First described in the 1930s in the USA, IB research has been dominated by the extensive genetic variation exhibited by the surface spike (S) protein gene, recognised half a century ago as antigenic variation. Specifically, virus neutralisation tests revealed the existence of serotypes (currently numbering dozens), which are poorly cross-protective [9,17,21,29,31,34,36,37,40,49,61,63,82].…”
Section: Introductionmentioning
confidence: 99%